Multiply the first equation by 5 and add the twice the second equation.

5(0.3x - 0.2y) + 2(0.5x + 0.5y) = 5(4) + 2(85/19)

1.5x - 1.0y + 1.0x + 1.0y = 20 + 170/19

2.5x = 550/19

x = (550/2.5)/19 = 220/19

Substituting this value into the second equation, we get

0.5(220/19) + 0.5y = 85/19

110/19 + 0.5y = 85/19 (eliminate parentheses)

0.5y = -25/19 (subtract 110/19)

y = (-25/0.5)/19 = -50/19 (divide by the y coefficient and evaluate)

The solution is

5(0.3x - 0.2y) + 2(0.5x + 0.5y) = 5(4) + 2(85/19)

1.5x - 1.0y + 1.0x + 1.0y = 20 + 170/19

2.5x = 550/19

x = (550/2.5)/19 = 220/19

Substituting this value into the second equation, we get

0.5(220/19) + 0.5y = 85/19

110/19 + 0.5y = 85/19 (eliminate parentheses)

0.5y = -25/19 (subtract 110/19)

y = (-25/0.5)/19 = -50/19 (divide by the y coefficient and evaluate)

The solution is

**(x, y) = (220/19, -50/19)**.